2013
DOI: 10.1556/imas.5.2013.1.5
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of vascular cell adhesion molecule-1 and high-sensitive C-reactive protein in normal and preeclamptic pregnancies

Abstract: Abstract:Background: Preeclampsia is characterized by hypertension, dyslipidemia, and systemic inflammatory response. The aim of this study was to determine the level of serum level of soluble vascular cell adhesion molecule-1 (sVCAM-1) and high-sensitive C-reactive protein (hsCRP) in preeclampsia and to compare normal pregnant, mild preeclamptic, and severe preeclamptic women. Methods: A cross-sectional study was conducted to determine the plasma concentrations of sVCAM-1 and hsCRP in peripheral blood obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Redman et al initially proposed that the features of the systemic inflammatory response observed in normotensive pregnant women are also seen in PE women, but in a greater intensity [ 5 ]. Accordingly, several studies have described increased activation of circulating leukocytes, abnormal immune cell phenotype and higher pro-inflammatory markers levels, such as C-reactive protein (CRP), in PE compared to normotensive pregnancy [ 6 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Redman et al initially proposed that the features of the systemic inflammatory response observed in normotensive pregnant women are also seen in PE women, but in a greater intensity [ 5 ]. Accordingly, several studies have described increased activation of circulating leukocytes, abnormal immune cell phenotype and higher pro-inflammatory markers levels, such as C-reactive protein (CRP), in PE compared to normotensive pregnancy [ 6 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to some studies, the serum levels of two inflammatory markers (namely, sICAM-1 and sVCAM-1) in women with a history of preeclampsia have been elevated (25). Previous studies conducted by the current research team showed that the level of this factor was significantly higher in patients with severe preeclampsia than patients with mild preeclampsia and normal pregnant women (17,18). It seems that these two inflammatory markers indicate preeclampsia-induced endothelial dysfunction in previous pregnancies.…”
Section: Immune System and Preeclampsiamentioning
confidence: 67%
“…Findings showed that the patient with severe preeclampsia had far higher levels of hs-CRP than patients with mild preeclampsia and normal pregnant women, indicating a significant between-groups difference. This implies that preeclampsia is an inflammatory trend that severely stimulates the immune system (17,18). Studies also show that the injection of TNF-α to pregnant mice increases blood pressure (19); in addition, TNF-α has a role in regulated transcription of platelet-derived growth factor (PDGF) and endothelin 1 (ET-1).…”
Section: Immune System and Preeclampsiamentioning
confidence: 99%
“…In contrast, other studies report no significant changes in CRP levels between normotensive and pre‐eclamptic women 20,22 . Reports also indicate elevated hs‐CRP level in severe PE cases as compared to mild cases 31,34–36,10 . Majority of the studies indicate that hs‐CRP could be used as a marker for the detection of PE and suggest that hs‐CRP may be utilized as a significant indicator of severity of PE at third‐trimester pregnancy (30–39 weeks) 16,17,29,37 .…”
Section: Discussionmentioning
confidence: 99%